The world breaks in two: thinking through HIV in creative writing practice towards an aesthetics of post-crisis. Issue 2 (3rd April 2021) - Scott, Ronnie
ABSTRACT: How should creative writers, including HIV-negative writers, think through HIV as a livable illness? What is the potential for writing gay fiction in an era of 'post-crisis'? This creative writing research draws links between literary modernism's roots in crisis and the roots of contemporary gay realist fiction in the AIDS crisis. It suggests these origins place similar demands on writers to re-conceive elements of fiction. This paper, primarily, outlines challenges of representing HIV in contemporary fiction, and then suggests that contemporary HIV's history of crisis provides ways to address these challenges, that the challenges may be productive. Because HIV in contemporary life is doubly invisible – viral loads may be undetectable, and the ongoing crisis can be understood as marginal or tactically historicised – aspects of creative writing after antiretrovirals exist in conversation with uncertainty, including elements that are otherwise put to representative use. By looking at some examples of post-crisis writing in contemporary gay realist fiction, the paper establishes the potential for HIV-positive representations to shift fiction-writing practice, bringing aspects of the novel such as time, metaphor and textual representation towards an aesthetics of post-crisis.